Development of Teaching Materials Based on Local Excellences of South Sumatera for Science Learning in Elementary School - Suratmi, Suratmi; Laihat, Laihat; Santri, Didi Jaya (Jurnal Penelitian dan Pembelajaran IPA, 2018)
This research is aims to develop the local excellences-based teaching materials of South Sumatera for science learning in elementary school. This teaching materials are designed and manufactured with local pre-eminent items in South Sumatra and adapted to the subject matter taught in science learning in elementary school. This research is a development research using ADDIE development model and Tessmer evaluation method. The development stages in this research include analysis, design, development, implementation, and evaluation. Evaluation of prototypes is conducted by: self evaluation, expert reviews, one-to-one evaluation, small group evaluation, and field test evaluation. Prototypes are validated by experts in materials, constructs, language, and media. The instruments used are questionnaires, observation sheets, test results and product assessment sheets. The result of the research shows that the teaching materials based on local excellences of South Sumatera are valid and after being tested in one to one, small group evaluation, field test evaluation of this teaching materials are considered practical. In conclusion, the teaching materials based on local excellences of South Sumatra are feasible to be used for science learning in elementary school.